A sequence of pain: feminist issues within Laila Al-Othman’s Ṣamt al-Farāshāt [silence of the butterflies] - Khaled Igbaria (Cogent Social Sciences)
This study discusses how Laila Al-Othman engages with issues to determine the nature of her feminist agenda. The different ways in which her novel, Ṣamt al-Farāshāt [Silence of the Butterflies], addresses several feminist issues, mainly forced marriage, rape and sexual abuse, gender-based physical sexual violence, and enforced silence, are explored. This paper focuses on demonstrating social obstacles and continuous trauma caused by a sequence of pain experienced by Arab females in their patriarchal society. It explores the freedom granted to these women in different aspects of life, including their sexuality within a marriage, even if temporarily. This study argues that the novel reveals a sustained effort to raise the banner of feminism and a strong desire to liberate Arab women from patriarchal domination. Al-Othman successfully and uniquely represents women as victims of gender-based traumatic sexual and physical violence, forced silence, and general oppression in patriarchal Arab society, who need help, support, protection, and liberation. They are not represented as independent or free. Methodologically, it employs a qualitative literary analysis in addition to trauma theory psychoanalysis, concentrating on feminist issues highlighted in the novel. The narrative techniques are not a focus of this study.